In vitro α-glucosidase inhibition and antioxidant activities of partially purified Antidesma bunius fruit and Gynura nepalensis leaf extracts - Noel Quiming, Joannes Luke Asis, Marilou Nicolas, Dhennis Versoza, Michael Russelle Alvarez (Journal of Applied Pharmaceutical Science, 2016)
Diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels. Current treatments involve the use of sulfonylureas, α-glucosidase inhibitors, and other synthetic drugs. The study demonstrated the α-glucosidase inhibition and antioxidant properties of partially purified ethanolic extracts of Antidesma bunius fruits and Gynura nepalensis leaves, as possible herbal drug candidates. After ethanol extraction, the extracts were fractionated using normal phase liquid column chromatography, with elution solvents ethyl acetate, methanol and water. Fractionation resulted in five fractions for A. bunius (A1, A2, A3, A4 and A5) and seven fractions for G. nepalensis (G1, G2, G3, G4, G5, G6 and G7). Fraction G1 showed the highest α-glucosidase inhibition activity (90.61±8.05%) and possibly acted via a mixed mode of inhibition. For the antioxidant activities, Fraction A1 exhibited highest radical scavenging activity via DPPH assay (97.39±2.48%), Fraction G7 exhibited highest iron (II)-chelating activity (95.85±1.46%) and Fraction G6 exhibited highest ferric-ion reducing activity via FRAP assay (272.60 μg/mL FeSO4 equivalents). Phytochemical screening revealed that flavonoids and tannins were common among all fractions. The results demonstrated the potential of these plants as an antidiabetic herbal treatment. However, further studies needs to be done, specifically focusing on isolating the active component(s), structure and mechanism elucidation and toxicity assays.
Keywords: Diabetes mellitus, Antidesma bunius, Gynura nepalensis, partial purification, &alpha; -glucosidase inhibition activity, antioxidant activity.